Moral Integrity of Pandita Magabudhi in Promoting Religious Moderation - Metta Dewi (Jurnal Pendidikan Indonesia, 2026)
In Indonesia’s multicultural society, frictions and conflicts among religious communities persist due to the emergence of extremist interpretations of religion. In this context, this study aims to comprehensively examine the dynamics of the Buddhist Religious Institution of the Indonesian Theravada Buddhist Council (MAGABUDHI). This research employs an interpretative qualitative approach, presented through descriptive and interpretative analysis. Primary data were obtained from key informants, consisting of the Chairperson of the Regional Board of MAGABUDHI, six religious leaders, and six members of MAGABUDHI. Secondary data were derived from relevant literature. Data were collected through observation, in-depth interviews, and document analysis. The research instruments included interview guidelines, audio recording devices, and visual recording tools. Data analysis was conducted using qualitative descriptive techniques, encompassing data reduction, data display, and conclusion drawing and verification. The findings reveal three main aspects. First, the dynamics of MAGABUDHI Pandita are influenced by both internal and external factors. Second, the forms of these dynamics encompass the processes of recruitment, guidance, and activities of MAGABUDHI Pandita. Third, the dynamics of MAGABUDHI Pandita have significant implications for the social and religious life of Buddhist communities in Jakarta. Through the consistent efforts of MAGABUDHI Pandita in fostering moral values and strengthening integrity in guiding their communities, the balanced and just practice of religious teachings can be realized. This study concludes that MAGABUDHI Pandita actively promote religious moderation by encouraging their followers to embrace a religious orientation grounded in the Middle Way (Majjhima Paṭipadā), emphasizing moderation and a return to the essential purpose of religious teachings, namely, the humanization of humanity.